Роль динамики опасных факторов пожара в патогенезе отравления человека на пожаре - Puzach, С.; Smagin, А.; Lebedchenko, О.; Doan, Вьет; Polevoda, Иван; Poloz, Денис; Osyaev, Владимир; Kuz'mitskiy, Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The analysis of toxic gases danger produced by combustion of burning load is presented. The calculations of dangerous factors dynamic for indoors fire have been performed using both integral and field models. It has been stressed the sufficient influence of highly toxic gases, in particular, acrolein as dangerous factors of fire. It is noted that existing database on burning load should be added with the highly toxic gases. It is emphasized the importance of individual approach in rendering of the medical care to fire victims demanded by highly toxic gases which depend on burning load type.